2008
DOI: 10.1021/ja7114053
|View full text |Cite
|
Sign up to set email alerts
|

“Clickable” Metal−Organic Framework

Abstract: We demonstrated the metal-organic framework bearing the azide group in the organic linkers and in situ click reactions with some small alkynes. The XRPD patterns indicated that the click reaction proceeded without any decomposition of the original MOF network. Controlling the organic linkers and incorporation of the azide groups should provide the designer-made MOFs that have controlled molecular cavities with the desired steric dimensions and functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(166 citation statements)
references
References 21 publications
(11 reference statements)
2
160
0
3
Order By: Relevance
“…In 2008, Sada s group [21] demonstrated that a MOF composed of a strut with two benzyl azides could be chemically modified with the CuAAC reaction by using a variety of small molecule alkynes. Subsequently, in 2009, Hupp and co-workers [22] went on to show that a MOF with pendant alkyne functionalities in its struts could be functionalized in a selective manner.…”
Section: 3-dipolar Cycloadditions Of Azides With Alkynesmentioning
confidence: 99%
“…In 2008, Sada s group [21] demonstrated that a MOF composed of a strut with two benzyl azides could be chemically modified with the CuAAC reaction by using a variety of small molecule alkynes. Subsequently, in 2009, Hupp and co-workers [22] went on to show that a MOF with pendant alkyne functionalities in its struts could be functionalized in a selective manner.…”
Section: 3-dipolar Cycloadditions Of Azides With Alkynesmentioning
confidence: 99%
“…Nowadays, there are some predominant methods that are in use to chemically modify surfaces, due to the smooth chemically conditions needed and the wide range of functional groups that can be introduced: the click chemistry [142][143] and the peptide coupling. [119] More recently, some new techniques were proposed to enhance and diversify the number of method that can be used to chemically modify surfaces.…”
Section: The Sonogashira Reactionmentioning
confidence: 99%
“…[143] Often, the first step is the introduction of a functional group via a suitable organic molecule as self assembled monolayer (SAM) on a noble metal substrate, [230][231] silicon or silicon oxide surfaces [125] [127] or as coating ligand for nanoparicles. [152] After the introduction of a chemically addressable surface layer, efficient chemical conditions such as click chemistry [142][228] [232] or peptide coupling [119] have been applied to further diversify the exposed surface functionality.…”
Section: Platinum Electrode Modificationmentioning
confidence: 99%
“…An azide-appended MOF exhibits pore surface decoration upon reaction with small alkynes 35 , whereas an MOF bearing trimethylsilane-protected acetylene units allows a selective deprotection and a selective decoration of the exterior and interior surfaces with ethidium bromide and phenyl groups, respectively, by reaction with the corresponding azide compounds 36 . Despite these achievements, density control of the functional surface groups in MOFs has not been obtained.…”
mentioning
confidence: 99%